2022
DOI: 10.1128/spectrum.02760-21
|View full text |Cite
|
Sign up to set email alerts
|

In Streptococcus thermophilus, Ammonia from Urea Hydrolysis Paradoxically Boosts Acidification and Reveals a New Regulatory Mechanism of Glycolysis

Abstract: Finding that ammonia-generating enzymes, such as urease, and exogenous ammonia act on phosphofructokinase activity shed new light on the regulatory mechanisms that govern glycolysis. Phosphofructokinase is the key enzyme known to exert a regulatory role on glycolytic flux and, therefore, ammonia as an effector of phosphofructokinase acts, in cascade, modulating the glycolytic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In our experiments, we observed that adding ammonium citrate or ammonium chloride to CDM hindered cell growth; similarly, it is reported that ammonium chloride was much less effective than urea or ammonia at promoting acidification in S. thermophilus. 15 This is because directly added NH 4 + cannot combine with protons and achieve cytoplasmic alkalinization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, we observed that adding ammonium citrate or ammonium chloride to CDM hindered cell growth; similarly, it is reported that ammonium chloride was much less effective than urea or ammonia at promoting acidification in S. thermophilus. 15 This is because directly added NH 4 + cannot combine with protons and achieve cytoplasmic alkalinization.…”
Section: Discussionmentioning
confidence: 99%
“…14 Nevertheless, a novel study has proposed that NH 4 + may enhance glycolysis and lactic acid fermentation by acting as an activator of phosphofructokinase. 15 These findings have prompted a reassessment of the role of urease in S. thermophilus. The unfavorable impact of urease on fermentation processes is attributed to unpredictable acidification rates, resulting from variable urea concentrations in different milk batches.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the partitioning between lactate and mixed-acid products was likely regulated at the metabolic level instead of at the transcriptional level ( Paixao et al., 2015 ). Correspondingly, the additional NADH in vivo synthesized by the fragmentary TCA cycle is used for homolactic fermentation of pyruvate and contributes to a balanced NAD + /NADH ratio that controls the shift from homolactic to mixed-acid fermentation in Lactococcus lactis , S. pneumoniae , Streptococcus thermophilus , and perhaps in S. suis ( Willenborg et al., 2015 ; Arioli et al., 2022 ). We speculated that the inhibited fragmentary TCA cycle reduces the yield of NADH and leads to the imbalance of the ratio and the transformation of fermentation manner in glycogen cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Urease rather has a key role in streamlining the energetic metabolism of S. thermophilus and specifically by acting on glycolysis regulation. [ 20–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Urease rather has a key role in streamlining the energetic metabolism of S. thermophilus and specifically by acting on glycolysis regulation. [20][21][22] In human microbiota, since the discovery of Helicobacter pylori, microbial ureases have been found to play a key role in the pathogenetic traits of several bacteria. [23] Several studies showed through a metagenomic approach that microbial ureases led to dysbiosis of the gut microbiota and that urease-genes are enriched in patients with irritable bowel syndrome (IBS) and depression.…”
Section: Introductionmentioning
confidence: 99%